Mangrove Syrup Making, Personal Selling, and Branding Training for Hani MSMEs in Langsa Lama Village: Pelatihan Pembuatan Sirup Mangrove, Personal Selling, dan Branding Untuk UMKM Hani di Desa Langsa Lama - Uci Dwi Cahya; Zulfikri Zulfikri; Weni Astari; Husaini Husaini; Maulida Sari; Dede Gustian (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
This activity aims to increase the production and marketing capacity of Hani MSMEs in Langsa Lama Village through training in making mangrove-based syrup which is integrated with personal selling and branding strategies. This is based on the potential of mangrove resources which are abundant but have not been utilized optimally, as well as the limitations of business actors in product processing and marketing. Activities were carried out using a descriptive qualitative approach with data collection techniques in the form of observation, interviews and documentation. The results of the activity showed an increase in participants' skills in processing mangroves into better quality syrup, marked by improvements in aspects of taste, color and product cleanliness. Apart from that, implementing a personal selling strategy has a positive impact on business actors' communication skills in offering products directly, thereby increasing self-confidence and sales opportunities. In the branding aspect, there have been significant changes to the appearance of the product through improved packaging design and more informative labeling, thus increasing the attractiveness and selling value of the product in the market. Overall, the integration of production training and marketing strategies has proven to be effective in improving the technical and managerial capabilities of MSME players. Therefore, this training model can be used as an alternative in efforts to empower MSMEs based on local potential to increase competitiveness and business sustainability.